Rapid quantitative screening of 15 synthetic cannabinoids in urine using direct analysis in real time tandem mass spectrometry: Screening method validation and cross-correlation study with liquid chromatography tandem mass spectrometry - Jenna Covey; Alex Maggitti; William Fatigante; Francois Espourteille; Holly Lombardo; Terry Bates (Green Analytical Chemistry)
Preliminary screening methods for detection of urine-based drugs of abuse are typically selected based on their ease of automation, cost effectiveness, and ability to deliver rapid results. As such, immunoassay-based testing approaches are commonly employed in routine drug screening workflows; however, these methods suffer from significant drawbacks, including cross-reactivity issues that can lead to false positives and false negatives, affecting the accuracy and reliability of results. The lack of selectivity inherent to IAs necessitates subsequent costly and time-consuming chromatography-based confirmatory testing. In this work, we report on the development of a fast, chromatography-free Direct Analysis in Real Time-tandem mass spectrometry-based (DART-MS/MS) screening approach for 15 synthetic cannabinoids and associated metabolites in urine. The proposed DART-MS/MS screening method effectively measured 15 targeted synthetic cannabinoids in 96 samples with a throughput of 23 s per sample, low limits of detection (< 1 ng/mL), high inter- and intra-day precision (≤ 20 % RSD), and high accuracy (≤ ± 20 % bias). These performance metrics fall within the acceptable ranges for urine screening analyses as set forth by American National Standards Institute/Academy Standards Board (ANSI/ASB) guidelines and demonstrate performance comparable to LC-MS/MS confirmatory methods. Validation experiments with authentic urine samples confirmed positive for one or more target analytes indicated good correlation for quantitation of synthetic cannabinoids as measured by DART-MS/MS versus liquid chromatography-tandem mass spectrometry (LC-MS/MS).